Pengaruh Transparansi dan Akuntabiitas Laporan Pertanggungjawaban Keuangan terhadap Pengelolaan Anggaran Dana BOS di SD Negeri Cibeber 1, 2, 3, dan 4 - Nugraha, Bagas; Hidayat, Asep Iwa; Suryaman, Warman (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of the study was to find out the effect of transparency and accountability of financial reporting on School Operational Assistance (BOS) funds at SDN Cibeber 1, 2, 3 and 4. Quantitative methods were used in which primary data was obtained from distributing questionnaires using Google Forms with linear regression analysis techniques. multiples whose data processing is assisted by SPSS software. The results of this study show that there is an influence between accountability on the management of BOS funds, but there is no significant effect of transparency on the management of BOS funds. Nonetheless, both accountability and transparency simultaneously have a significant effect on Accountability Reporting and a BOS at SDN Cibeber 1, 2, 3 and 4. The effect of transparency and accountability can also be seen from the calculation results and the coefficient of determination (R-Square) of 0.673 (67 .3%) where the rest are other variables that influence the management of BOS funds but were not examined in this study.